1997
DOI: 10.1016/s0735-1097(97)82537-5
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis Plus Aortic Counterpulsation: Improved Survival in Patients Who Present to Community Hospitals With Cardiogenic Shock

Abstract: Survival may be enhanced and transfer for revascularization facilitated when community hospitals use both thrombolysis and IABP to treat patients with acute MI complicated by cardiogenic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
10

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(58 citation statements)
references
References 23 publications
2
44
0
10
Order By: Relevance
“…Despite this, mortality at the 6 month follow-up (13%) was not significantly higher and compares favourably to previous reports in similar patients, with mortality rates of 15% and 40% [8,14,17] . This low mortality might be attributed to the intra-aortic balloon pump, which has been shown to be of value in patients with cardiogenic shock [14] , but might also be related to the high rate of repeat revascularization within 6 months.…”
Section: Routine Vs Elective Use Of Intra-aortic Balloon Pumpsupporting
confidence: 84%
“…Despite this, mortality at the 6 month follow-up (13%) was not significantly higher and compares favourably to previous reports in similar patients, with mortality rates of 15% and 40% [8,14,17] . This low mortality might be attributed to the intra-aortic balloon pump, which has been shown to be of value in patients with cardiogenic shock [14] , but might also be related to the high rate of repeat revascularization within 6 months.…”
Section: Routine Vs Elective Use Of Intra-aortic Balloon Pumpsupporting
confidence: 84%
“…Barron et al illustrated that patients with AMI complicated by CS may have substantial benefit from IABP when used in combination with thrombolysis, which decreased the odds of death by 18% [2]. Another 2 trials also showed that thrombolysis plus IABP could improve survival in these patients [11,12]. Similar to previous research, although there was a trend towards a few cases of bleeding and vascular complications, our present study showed that IABP therapy could attenuate the death rate markedly in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Multiple studies have suggested mortality benefits of IABP in patients with cardiogenic shock complicating AMI. 3,7,8,20,21 The American College of Cardiology (ACC) and the American Heart Association (AHA) recommend the use of IABP in patients with shock refractory to pharmacological therapy and as a stabilizing measure for urgent revascularization. 22 Nevertheless, the use of IABP in the treatment of cardiogenic shock remains remarkably low.…”
Section: Discussionmentioning
confidence: 99%